2021
DOI: 10.18632/aging.202573
|View full text |Cite
|
Sign up to set email alerts
|

No difference in hepatocellular carcinoma risk in chronic hepatitis B patients treated with tenofovir vs entecavir: evidence from an updated meta-analysis

Abstract: Whether tenofovir disoproxil fumarate (TDF) is superior to entecavir in reducing hepatocellular carcinoma (HCC) risk among treatment-naïve chronic hepatitis B (CHB) patients remains controversial. We aimed to clarify this controversy. Several databases, including PubMed and Embase, were retrieved through November 2020. Cohort studies comparing the effectiveness of TDF and entecavir in reducing HCC incidence among treatment-naïve CHB patients were included if they reported multivariable-adjusted or propensity-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…The difference in the follow-up duration due to the asynchronous introduction of the two treatments may cause a bias in either direction. Previous meta-analyses by Tseng et al [33] and Li et al [40] also noticed this point, and they performed subgroup analyses based on follow-up duration. In studies with a follow-up duration of ETV that was longer than TDF by more than one year, TDF was significantly associated with a lower risk of HCC (aHR = 0.69; 95%CI: 0.61-0.79).…”
Section: Third Issue: Differences In the Follow-up Timementioning
confidence: 77%
See 4 more Smart Citations
“…The difference in the follow-up duration due to the asynchronous introduction of the two treatments may cause a bias in either direction. Previous meta-analyses by Tseng et al [33] and Li et al [40] also noticed this point, and they performed subgroup analyses based on follow-up duration. In studies with a follow-up duration of ETV that was longer than TDF by more than one year, TDF was significantly associated with a lower risk of HCC (aHR = 0.69; 95%CI: 0.61-0.79).…”
Section: Third Issue: Differences In the Follow-up Timementioning
confidence: 77%
“…The results of the meta-analyses published so far are summarized in Table 1. Although the studies and patients included in the 11 meta-analyses were slightly different, most of the meta-analyses except for two (Tseng et al [33] and Yuan et al [34] ) reported that TDF was superior to ETV in preventing HBV-associated HCC when the adjusted HR was pooled. Most meta-analyses performed subgroup analyses and/or metaregression to address between-study heterogeneity.…”
Section: Meta-analysesmentioning
confidence: 99%
See 3 more Smart Citations